Morfogénesis de los gametofitos de especies mexicanas de Pleopeltis (Polypodiaceae, subfamilia Pleopeltoideae) - Reyes Jaramillo, Irma; Pérez-García, Blanca; Mendoza Ruiz, Aniceto (Revista de Biología Tropical, 2003)
the development and morphology of the gametophytes of seven species of ferns from genus Pleopeltis are described and compared. The spore germination is Vittaria-type in P. astrolepis, P. crassinervata, P. macrocarpa, P. polylepis and P. revoluta. For P. angusta and P. mexicana it was proposed a new germination pattern is Pleopeltis-type. The prothallial development is Drynaria-type in P. astrolepis, P. crassinervata, P. macrocarpa, P. polylepis and P. revoluta and Ceratopteris-type for P. angusta and P. mexicana. The gametangia are typical of the leptosporangiate ferns, sporophytes after six and a half months in culture did not appeared.